Safety Conditions and Practices in Secondary Agricultural Mechanics Programs - Perry, Dustin K.; Williams, Robert E.; Anderson, Ryan G. (Journal of Agricultural Systems, Technology, and Management, 2012)
The purpose of this study was to determine if secondary agricultural mechanics laboratories were perceived to be safe by the teachers who utilize them. This study also sought to determine the most common safety violations found in a high school agricultural mechanics laboratory. The health belief model was utilized as the framework for this study. A web-based questionnaire using the National Institute for Occupational Safety and Health (NIOSH) checklist for secondary agricultural science laboratories was developed to assess teachers’ perceptions regarding safety in their secondary agricultural mechanics laboratory. Four specific areas of concern related to safety practices and conditions in agricultural mechanics laboratories were identified. They included signage, storage of oxygen and fuel gas cylinders, noise levels, and disconnecting switches on arc welding machines.